MOTIVASI BELAJAR SISWA DALAM MENGIKUTI PEMBELAJARAN PENJASORKES SISWA KELAS V SD NEGERI 019 SUKARAMAI TAPUNG HULU - Sri Marliana; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of holding the research was to determine the level of learning motivation of grade V SD Negeri 019 Sukaramai in participating in physical education learning. This type of research is descriptive research, which is one type of research whose specifications are systematic, planned, and clearly structured from the start to the research design. This research was conducted at SD Negeri 019 Sukaramai, Jl. Kampung Baru Paitan, Kasikan Village, Tapung Hulu. The research time was carried out for 9 months from June 2020 to March 2021. Based on the results of the research as a whole, students 'learning motivation in participating in physical education learning for class V SD Negeri 019 Sukaramai Tapung Hulu, it can be concluded that the percentage for indicators of students' intrinsic motivation to learn in participating in learning Penjasorkes 56% with a total of 14 students in the "enough" category. For extrinsic motivation indicators for student learning in participating in Physical Education learning by 92% with a total of 23 students in the category of being in the "enough" category. So the motivation for student learning in participating in physical education learning for class V SD Negeri 019 Sukaramai Tapung Hulu was 84% with a total of 21 students in the "enough" category. Key Words: Learning Motivation, Health and Recreation Physical Education